2014
DOI: 10.1038/ncomms5483
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted auto-regulation of the spliceosomal gene SNRPB causes cerebro–costo–mandibular syndrome

Abstract: Elucidating the function of highly conserved regulatory sequences is a significant challenge in genomics today. Certain intragenic highly conserved elements have been associated with regulating levels of core components of the spliceosome and alternative splicing of downstream genes. Here we identify mutations in one such element, a regulatory alternative exon of SNRPB as the cause of cerebro–costo–mandibular syndrome. This exon contains a premature termination codon that triggers nonsense-mediated mRNA decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
81
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 36 publications
2
81
0
2
Order By: Relevance
“…Interestingly, five mutations in the same region have recently been identified in another series of CCMS patients [Lynch et al, 2014] and three of them are identical to our patients variants (P1, P2, P4).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, five mutations in the same region have recently been identified in another series of CCMS patients [Lynch et al, 2014] and three of them are identical to our patients variants (P1, P2, P4).…”
supporting
confidence: 84%
“…Interestingly, Saltzman et al [] demonstrated that 12‐base segments deletion including these two regions leads to an increase in inclusion of the alternative exon. Moreover, Lynch et al [] reported increased expression of the PTC‐containing transcript associated with decreased overall expression of SNRPB in CCMS case fibroblasts. Transcript 3 is essential for SmB autoregulation.…”
mentioning
confidence: 99%
“…Interestingly, mutations in genes encoding other components of the spliceosome have been linked to craniofacial disorders. They include mutations in EFTUD2 (Lines et al, 2012), SNRPB (Lynch et al, 2014) and TXNL4A (Wieczorek et al, 2014), which cause related but distinct syndromes known as MFD with microcephaly (OMIM #610536), cerebro-costo-mandibular syndrome (OMIM #117650), and Burn-McKeown syndrome (OMIM #608572) respectively, suggesting that spliceosomopathies may underlie the etiology of some forms of MFD (Lehalle et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…During assembly of the U2 pre-spliceosomal complex, SAP49 binds to the pre-mRNA just upstream of the branch point sequence and plays a crucial role in tethering the U2 snRNP to the branch site during the splicing process (Champion-Arnaud and Reed, 1994). Mutations in genes encoding other components of the spliceosome, such as EFTUD2 (Lines et al, 2012), SNRPB (Lynch et al, 2014) and TXNL4A (Wieczorek et al, 2014) also cause craniofacial disorders, suggesting that defects in mRNA processing may underlie the etiology of some forms of MFD (Lehalle et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Cerebrocostomandibular syndrome (CCMS; MIM 117650)-affected individuals exhibit Robin sequence and characteristic rib defects and harbor mutations in SNRPB (9,10), while Richieri-Costa-Pereira syndrome (RCPS; MIM 268305) is characterized by midline mandibular cleft, Robin sequence, radial and tibial abnormalities, and often intellectual disability, and is associated with mutations in EIF4A3 (11) (Fig. Along the same lines, defects in mRNA processing have recently been established as the basis of two syndromes in which the mandible is severely affected.…”
mentioning
confidence: 99%